Accounting Offshoring: The Role of Emotional Intelligence - Gaurav Gupta; Stephen B. Salter; Philip A. Lewis (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: The primary purposes of this paper are to compare the emotional intelligence levels of Americans and Indians and explore the potential impacts of these differences in the offshoring relationships. Motivation: The continued growth of the Indian economy and its legions of inexpensive English-speaking graduates has made India a global leader in business process offshoring. U.S. companies, including accounting firms, routinely offshore a variety of their business functions to India. However, the effective functioning of these offshoring relationships has been offset by perceptions of the Indian providers' poor communication and ineffective management training (Downey, 2018; Jain, 2015; Mayur, James, and Swamynathan, 2015). We believe that a culture-influenced behavioral factor known as Emotional Intelligence (EI) has resulted in less than the optimal performance outcome for the U.S. public accounting firms in these offshoring relationships. Data: Using MSCEIT EI inventory, we collect data from 197 master's students enrolled in accounting courses in India and the U.S. on four branches of EI. Findings: Our results indicate that the Indian students have statistically lower levels of EI than the U.S. students. We discuss the implications for public accounting firms that offshore to India and advocate for the inclusion of the EI related coursework in Indian master's programs and firm training. Contribution: Using a well-established inventory of EI, our study provides a deeper understanding of the cultural EI differences between Americans and Indians, and the possible implications for the offshoring environment.
Keywords: M41; 650; India; emotional intelligence; audit; culture; offshoring; Big 4 accounting firms